Reciprocal Signaling Between Translational Control Pathways and Synaptic Proteins in Autism Spectrum Disorders - Santini, Emanuela (Sci Signal, 2014)
Autism spectrum disorder (ASD) is a heterogeneous group of heritable neurodevelopmental disorders whose symptoms, which include deficits in social interaction skills, impaired communication ability, and ritualistic-like repetitive behaviors, appear in early childhood and continue throughout life. Genetic studies have revealed at least two clusters of genes frequently associated with ASD and intellectual disability: genes encoding for proteins involved in translational control and proteins involved in synaptic function. We hypothesize that mutations occurring in these two clusters of genes interfere with interconnected downstream signaling pathways to cause ASD symptomatology. In this review, we focus on the monogenic forms of ASD caused by mutations in genes encoding for proteins that regulate translation and synaptic proteins. Specifically, we describe the function of these proteins, the intracellular signaling regulated by them, and the current mouse models utilized to characterize synaptic and behavioral features of these mutations. Finally, we summarize recent studies that have established a connection between these two signaling pathways in models of ASD and propose that dysregulation of one pathway has a detrimental impact of the other.